Sustained benefits of long-term biochar application for food security and climate change mitigation - Jingrui Yang; Longlong Xia; Kees Jan van Groenigen; Xu Zhao; Chaopu Ti; Weilu Wang; Zhangliu Du; Mingsheng Fan; Minghao Zhuang; Pete Smith; Rattan Lal; Klaus Butterbach-Bahl; et al. (Proceedings of the National Academy of Sciences, 2025)
Biochar application offers significant potential to enhance food security and mitigate climate change. However, most evidence stems from short-term field experiments (≤3 y), leaving uncertainty about the long-term sustainability of these benefits, especially with annual biochar additions to soils. To address this knowledge gap, we analyzed a global dataset from 438 studies (3,229 observations) and found that long-term annual biochar application (≥4 y) not only sustains but often enhances its benefits. These include improved crop yields (+10.8%), reductions in CH 4 (–13.5%) and N 2 O (–21.4%) emissions, and increased soil organic carbon content (+52.5%). In contrast, these benefits tend to diminish over time with single biochar applications due to the aging effect of biochar. Results from 29 global long-term experiments (4 to 12 y) confirm these sustained benefits for crop yield and greenhouse gas mitigation, although the magnitude of effects varies with soil properties, climate, and management practices. To maximize biochar’s long-term benefits for global food security and climate change mitigation, it is essential to develop viable strategies, such as applying biochar at intervals of several years while tailoring practices to local soil, climate, and cropping conditions.